Protein molecular surface triangulation based on Contour-Buildup algorithm - Jingqiao Zhang; Lin Wang (The 2014 2nd International Conference on Systems and Informatics (ICSAI 2014), 2014)
In this paper, we combine the Extraction Surface Atoms algorithm with the Contour-Buildup algorithm to generate a triangular mesh model for a protein's solvent-excluded surface. Only calculating and triangulating surface atoms can not only improve computational efficiency significantly, but also achieve better real-time property. Moreover, we improve the triangular method of convex spherical patches by using intermediate results of Contour-Buildup algorithm. Consequently, saddle patches and convex spherical patches can be connected seamlessly. As a result, we can obtain a uniform and seamless triangular mesh for a protein molecule.